Third-dimensional organ and tissue printing: techniques, applications, and limitations - Yang-Lee, Iria (2018)
Third-dimensional (3D) printing is the additive manufacturing process of a three-dimensional object, controlled by a computer program. Its three major stages are preprocessing, processing and postprocessing. In addition, with regard to processing, the different techniques for obtaining it include laser-assisted bioprinting, thermal printing using cartridges and bioink, direct-write bioprinting, and bioprinting using spheroids. Some of the general applications of the mentioned methods are hepatic and cardiac tissue manufacture, and myocytes differentiation, which are useful for advance in medicine and in the development of drugs. Even so, there are challenges to overcome and limitations related to them, including the adequate development of organs and tissues vasculature, and the fact of transplanting an organ obtained by bioprinting to a patient; besides, postsurgery care, considered as part of the immunovigilance. As a complement, a series of bioethical implications should be undertaken; among them, the implementation of informed consent is relevant in every step of the therapy to which the patient submits. This implies the creation of laws and guides to regulate the process.